MORAL VALUES IN MARGONDANG OF ANGKOLA ETHNIC - Haksa Romatua Pohan; M. Manugeren; Purwarno Purwarno (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
Margondang belonging to the ethnic of Angkola, becomes an important part of a celebration, especially in a wedding. Traditionally Angkola Ethnic Wedding can be said to be invalid if both families, either from the groom's family or the bride’s do not carry out this Margondang tradition. At the very first glance Margondang is a traditional dance called a tortor having movements as a medium of communication on moral values, intended not only for the bride and groom to live together, but for all the guests and participants present to be more sensitive in carrying out life. Sensitivity here is certainly related to the harmonious relationship among humans and between humans with nature so that prosperous and peaceful life can be obtained. This is the core of the implementation of Margondang tradition. This study aims at analysing the moral values of Margondang, conducted by means of descriptive qualitative research method. Data collection procedures are supported by observation, interview and questionnaire techniques, covering 20 respondents chosen randomly in randomly-selected weddings in Medan. The results show that there are three points of moral value in Margondang: brotherhood, respect and responsibility.